2011
DOI: 10.1186/1471-2156-12-89
|View full text |Cite
|
Sign up to set email alerts
|

qDTY 1.1 , a major QTL for rice grain yield under reproductive-stage drought stress with a consistent effect in multiple elite genetic backgrounds

Abstract: BackgroundDrought is one of the most important abiotic stresses causing drastic reductions in yield in rainfed rice environments. The suitability of grain yield (GY) under drought as a selection criterion has been reported in the past few years. Most of the quantitative trait loci (QTLs) for GY under drought in rice reported so far has been in the background of low-yielding susceptible varieties. Such QTLs have not shown a similar effect in multiple high- yielding drought-susceptible varieties, thus limiting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
300
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(341 citation statements)
references
References 48 publications
38
300
0
Order By: Relevance
“…Comparing the current results with previous studies, we found that QSnp1b affecting SpNP, detected in the region of 38493222-39565366 on chromosome 1 in this study, was mapped together with qDTY 1.1 affecting grain yield detected in N22 Â Swarna, N22 Â IR64, and N22 Â MTU1010 populations under drought stress (Vikram et al 2011), the QTL controlling leaf rolling, and relative water content (Price et al 2002b), as well OsCOIN (Liu et al 2007); OsNAC6 (Nakashima et al 2007); AP59 ); ARAG1 (Zhao et al 2010); OsTIFY11a (Ye et al2009); OsNAC045 (Xiao et al 2007;Zheng et al 2009 as QRvd1, QRvd1 and QDlr1 for root volume, root growth rate in volume, and number of days to leaf rolling under drought conditions (Yue et al 2006). The QTL QGyp2a for GYP detected in the region of 10693848-11540193 on chromosome 2 was mapped together with qDTY 2.1 affecting grain yield (Venuprasad et al 2009;Dixit et al 2012), the QTL for osmotic adjustment (Robin et al 2003), and the QRgvd2 for root growth rate in volume under drought conditions (Yue et al 2006).…”
Section: Effect Of Genetic Background On Detection Of Qtls For Dtsupporting
confidence: 69%
See 2 more Smart Citations
“…Comparing the current results with previous studies, we found that QSnp1b affecting SpNP, detected in the region of 38493222-39565366 on chromosome 1 in this study, was mapped together with qDTY 1.1 affecting grain yield detected in N22 Â Swarna, N22 Â IR64, and N22 Â MTU1010 populations under drought stress (Vikram et al 2011), the QTL controlling leaf rolling, and relative water content (Price et al 2002b), as well OsCOIN (Liu et al 2007); OsNAC6 (Nakashima et al 2007); AP59 ); ARAG1 (Zhao et al 2010); OsTIFY11a (Ye et al2009); OsNAC045 (Xiao et al 2007;Zheng et al 2009 as QRvd1, QRvd1 and QDlr1 for root volume, root growth rate in volume, and number of days to leaf rolling under drought conditions (Yue et al 2006). The QTL QGyp2a for GYP detected in the region of 10693848-11540193 on chromosome 2 was mapped together with qDTY 2.1 affecting grain yield (Venuprasad et al 2009;Dixit et al 2012), the QTL for osmotic adjustment (Robin et al 2003), and the QRgvd2 for root growth rate in volume under drought conditions (Yue et al 2006).…”
Section: Effect Of Genetic Background On Detection Of Qtls For Dtsupporting
confidence: 69%
“…The identification and introgression of QTLs for grain yield under reproductive-stage drought stress from landraces and wild progenitor species into elite rice varieties is a fast-track approach in breeding drought-tolerant rice varieties (Vikram et al 2011). However, very few DT rice varieties have been developed using MAS and released to farmers.…”
Section: Implications For Rice Breeding Of Dtmentioning
confidence: 99%
See 1 more Smart Citation
“…Such comparative analysis should target key morphological, physiological, anatomical, and agronomic traits throughout the crop growth cycle, as water deficit stress occurs at both early (vegetative stage) and late (reproductive stage) seasons in rice (Pandey et al, 2007). Extensive research efforts are currently ongoing to reduce the impact of water deficit stress during the reproductive stage in rice (Venuprasad et al, 2008;Verulkar et al, 2010;Vikram et al, 2011;Kumar et al, 2014) and in wheat (Olivares-Villegas et al, 2007;Lopes and Reynolds, 2010;Pinto et al, 2010). Therefore, our study focused on stress during the vegetative stage to identify key checkpoints that determine whole-plant responses of representative rice cultivars adapted to lowland, upland/aerobic, or water deficit conditions and of wheat cultivars with moderate to high water deficit tolerance.…”
mentioning
confidence: 99%
“…A large-effect QTL qDTY1.1 has been identified as having an effect on grain yield under severe lowland reproductive-stage drought across F3-derived populations developed from a cross between N22 and Swarma, N22 and IR64 and N22 and MTU1010 (Vikram et al, 2011). This QTL has also been reported in CT9993-5-10-1-M/IR62266-42-6-2 and Apo/IR64 populations Venuprasad et al, 2012a).…”
Section: Qtl For Yield and Yield Related-traits Under Droughtmentioning
confidence: 84%